THE INFLUENCE OF PRICE DISCOUNT, HEDONIC MOTIVATION, AND E-WOM ON IMPULSIVE BUYING OF FASHION PRODUCTS - Ariani, Wenda Ventika; Al Amin, Nur Hidayah; Wulandari, Fitri (Universitas Nusa Cendana, 2025)
This study seeks to investigate how price discounts, hedonic motivation, and electronic word-of-mouth (E-WOM) influence the impulsive buying of fashion items on TikTok Shop. The object of this study is Generation Z users of TikTok Shop resending in Sukoharjo Regency. This research employs a quantitative approach, utilizing surveys for data gathering and employing multiple linear regression analysis methods with the support of IBM SPSS 23 software for analysis. In this study, incidental sampling techniques were utilized, with a total of 200 respondents. The research findings indicate that partially, the variables of price discount, hedonic motivation, and E-WOM have a significant influence on impulsive buying. Furthermore, simultaneously price discounts, hedonic motivation, and E-WOM collectively affect impulsive buying. This study implies the necessity for ByteDance to maintain the TikTok Shop feature with marketing strategies that follow fashion trends and enhance sales promotion to drive impulsive buying by users. Keywords: Price Discount; Hedonic Motivation; E-WOM; Impulsive Buying